O papel das interações sociolinguístiscas professora-criança no desenvolvimento de crianças de 0 a 3 anos - Cruz, Solange Maria de Oliveira (2017)
This dissertation had as object of study the role of sociolinguistics teacher-child interactions in the development of children from 0 to 3 years. Our hypothesis is that the ideas concerning social interactions present in the historical-cultural theory, can bring important contributions to the educational work of the teachers of early childhood education, in particular with children from 0 to 3 years, contributing to their development as human beings.It was developed a search of bibliographical nature supplemented with analysis collected through observations and questionnaires along to a public institution of early childhood education. The theoretical framework was set up based on the ideas of Vygotsky (1995, 1996, 1998, 2001, 2004, 2007, 2010) and its employees, in addition to Brazilian authors who study the historical-cultural theory as Mello (2002, 2008, 2010, 2014), Oliveira (1992, 1993, 2010), Rego (2014), and others. The work aimed to search which aspects of the historical-cultural theory can assist in the guidance of the teachers relations with children from 0 to 3 years in early childhood education, in view of the contribution of these relationships for their development. The research pointed out that the teachers they deem important to establish a dialogue with children so that, among other things, they develop the language, especially the oral language, and learn to establish interactions and emotional links, confirming the importance of speech for human development, that is expressed in the theory. They also consider it is important to talk to the children as a means of promoting human development, in other words use of mediation, another important element of human development pointed to the historical-cultural theory, but they seem to ignore that speech is so inseparable linked to thought since no mention about it in their answers in the questionnaire applied. The early childhood education schools should promote sociolinguistics teacher-child interactions, based on their importance to human development. It hás hightly been indicated that the teachers need to know how occurs learning and human development occours, in particular the talks, since the birth, in order to organize activities that best behold the language teaching,fulfilling the various needs that children have, with views to the full development of their speech and how to be social.